(N|WOL@CIQ SOSTAWA GRANATOW \KLOGIT(B-(NSLANCEWYH I \KLOGIT(B-(NSLANCEMIGMATITOWYH KOMPLEKSOW (B:s ((NnA PRIM(B. (N\KLOGITOW sRED(B. (NuRALA(B) /s - (NbELKOWSKIJ(B, (NaNATOLIJ iWANOWI^s; (NiWANOW(B, (Ns(B.(Nn(B.s; (NuRALXSKIJ NAU^NYJ CENTR an sssrs ((NsWERDLOWSK (B:s (Nunc an sssr(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 165-181 (462 (NNAZW(B.)s
Keywords: (NgRANATY (B((NMINERALOG(B.)s; (NmINERALOGI^ESKIJ SOSTAWs; (N|KLOGITYs